Zoo animal welfare - Maple, Terry (Animal Welfare, 2013)
Zoo Animal Welfare thoroughly reviews the scientific literature on the welfare of zoo and aquarium animals. Maple and Perdue draw from the senior author's 24 years of experience as a zoo executive and international leader in the field of zoo biology. The authors' academic training in the interdisciplinary field of psychobiology provides a unique perspective for evaluating the ethics, practices, and standards of modern zoos and aquariums.  The book offers a blueprint for the implementation of welfare measures and an objective rationale for their widespread use. Recognizing the great potential of zoos, the authors have written an inspirational book to guide the strategic vision of superior, welfare-oriented institutions. The authors speak directly to caretakers working on the front lines of zoo management, and to the decision-makers responsible for elevating the priority of animal welfare in their respective zoo. In great detail, Maple and Perdue demonstrate how zoos and aquariums can be designed to achieve optimal standards of welfare and wellness.